2000
DOI: 10.1089/152702900320658
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Increases During Childhood and Decreases During Adulthood Among High Altitude Native Tibetans Residing at 3800–4200 m

Abstract: This report describes age differences in oxygen saturation throughout the life cycle in a sample of high altitude native Tibetans residing in villages at 3,800-4,200 m altitude in the Tibet Autonomous Region, China. Oxygen saturation of 3,812 Tibetans was measured by pulse oximetry and a subsample of 1,582 healthy, nonpregnant, nonsmokers from 1 week to 80 years of age was selected for analyses. Infants under 1 year of age had 5-6% lower oxygen saturation than the peak of 89.8% attained at 11 years of age. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
2
34
2
2
Order By: Relevance
“…These levels were even lower than those found in other studies at midaltitude (Lozano et al, 1992;Gamponia et al, 1998;Beall, 2000;Graham et al, 2008;Subhi et al, 2009), suggesting a decreasing trend of Sao 2 when altitude increased. The reduction of normal Sao 2 found at this altitude become the reference values used in the coast inappropriate for this population and remarks the importance of determining accurate reference values for children residing at very high altitude.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…These levels were even lower than those found in other studies at midaltitude (Lozano et al, 1992;Gamponia et al, 1998;Beall, 2000;Graham et al, 2008;Subhi et al, 2009), suggesting a decreasing trend of Sao 2 when altitude increased. The reduction of normal Sao 2 found at this altitude become the reference values used in the coast inappropriate for this population and remarks the importance of determining accurate reference values for children residing at very high altitude.…”
Section: Discussioncontrasting
confidence: 73%
“…This increase differs from that described in the Tibetan population, who typically experience a marked rise in Sao 2 levels during the first decade of life and then remaining stable after 11 yr (Beall, 2000). In other reports, Huicho and colleagues (2001) found a weak positive association between saturation and age from 4 to 18 yr.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Everyone in each household was invited to participate in a survey of oxygen saturation of hemoglobin that also involved providing information on factors known to influence oxygen saturation, including age, sex, pregnancy status, self-reported health status, self-reported symptoms of chronic obstructive lung disease, medications, and smoking behavior (see ref. 4 for details). A total of 95% of those encountered (Ϸ63% of the total number of residents) agreed to participate, and a total of 3,812 people provided pulse oximetry.…”
Section: Methodsmentioning
confidence: 99%
“…The examination of genetic and/or developmental origins of higher Sao 2 levels in highlanders contributes to the broader question of adaptation to high altitude Beall, 2000;Moore, 2001). Early studies conducted by Beall and colleagues (1994;1998) in Tibetans reported that Sao 2 showed significant heritability.…”
Section: Introductionmentioning
confidence: 99%